Serum Levels of IL-6 and TNF-α May Correlate with Activity and Severity of Rheumatoid Arthritis - Wei, Shi-Tong (Med Sci Monit, 2015)
BACKGROUND: We aimed to investigate the association of rheumatoid arthritis (RA) with interleukin 6 (IL-6) and tumor necrosis factor-α (TNF-α) through a meta-analysis. MATERIAL/METHODS: The case-control studies that investigated the association between RA and serum levels of IL-6 and TNF-α were retrieved strictly according to the inclusion and exclusion criteria. The statistical analysis was performed using STATA statistical software (Version 12.0, Stata Corporation, College Station, TX, USA). RESULTS: Fourteen studies were enrolled in our meta-analysis, with a total of 890 patients with RA and 441 healthy people as the controls. The results of this meta-analysis revealed that the serum IL-6 and TNF-α levels of RA patients were significantly higher than in the controls, and this difference was statistically significant (IL-6: SMD=2.40, 95% CI=1.57~3.24, P<0.001; TNF-α: SMD=1.93, 95% CI=1.23~2.64, P<0.001). According to ethnic subgroup analysis, the serum IL-6 and TNF-α levels of RA patients were also significantly higher compared with the controls in Asians and Caucasians (IL-6: Asians: SMD=3.64, 95% CI=2.16~5.12, P<0.001; Caucasians: SMD=0.75, 95% CI=0.47~1.02, P<0.001; TNF-α: Asians: SMD=2.74, 95%CI=1.58~3.91, P<0.001; Caucasians: SMD=0.81, 95% CI=0.50~1.11, P<0.001). CONCLUSIONS: IL-6 and TNF-α may play crucial roles in the activity and severity of RA.